2017
DOI: 10.1177/1744806917697011
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of nerve growth factor signaling in bone nociceptors and in an animal model of inflammatory bone pain

Abstract: Sequestration of nerve growth factor has been used successfully in the management of pain in animal models of bone disease and in human osteoarthritis. However, the mechanisms of nerve growth factor-induced bone pain and its role in modulating inflammatory bone pain remain to be determined. In this study, we show that nerve growth factor receptors (TrkA and p75) and some other nerve growth factor-signaling molecules (TRPV1 and Nav1.8, but not Nav1.9) are expressed in substantial proportions of rat bone nocicep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 101 publications
3
95
0
Order By: Relevance
“…Many of these mechanosensitive nerve fibers that detect and signal the initial fracture pain are located in the periosteum which is tightly opposed to the outer cortical wall of mineralized bone [36]. Previous studies have shown that many of the sensory nerve fibers that innervate the periosteum are mechanosensitive C and A-delta nociceptors [34, 37, 38, 39•] that rapidly respond to mechanical distortion of the adjacent bone or increased intraosseous pressure [37, 40, 41]. Following bone fracture, any movement or loading of the fractured bone would be expected to result in mechanical stimulation of mechanosensitive sensory nerve fibers that innervate the periosteum, mineralized bone, and marrow [27••, 28, 37, 42, 43].…”
Section: Mechanisms That Drive Bone Fracturementioning
confidence: 99%
See 4 more Smart Citations
“…Many of these mechanosensitive nerve fibers that detect and signal the initial fracture pain are located in the periosteum which is tightly opposed to the outer cortical wall of mineralized bone [36]. Previous studies have shown that many of the sensory nerve fibers that innervate the periosteum are mechanosensitive C and A-delta nociceptors [34, 37, 38, 39•] that rapidly respond to mechanical distortion of the adjacent bone or increased intraosseous pressure [37, 40, 41]. Following bone fracture, any movement or loading of the fractured bone would be expected to result in mechanical stimulation of mechanosensitive sensory nerve fibers that innervate the periosteum, mineralized bone, and marrow [27••, 28, 37, 42, 43].…”
Section: Mechanisms That Drive Bone Fracturementioning
confidence: 99%
“…Previous studies have shown that many of the sensory nerve fibers that innervate the periosteum are mechanosensitive C and A-delta nociceptors [34, 37, 38, 39•] that rapidly respond to mechanical distortion of the adjacent bone or increased intraosseous pressure [37, 40, 41]. Following bone fracture, any movement or loading of the fractured bone would be expected to result in mechanical stimulation of mechanosensitive sensory nerve fibers that innervate the periosteum, mineralized bone, and marrow [27••, 28, 37, 42, 43]. Thus, normally, non-noxious loading of the bone will distort the mechanosensitive nerve fibers so that even normally innocuous movement or loading of the fractured bone will now be perceived as a highly noxious event.…”
Section: Mechanisms That Drive Bone Fracturementioning
confidence: 99%
See 3 more Smart Citations